On Sw*-Normal Spaces - Abudllah, Laila S. (Sulaimani Journal for Pure and Applied Sciences, 2017)
The aim of this paper is to introduce and study a new class of spaces, called Sw*- normal spaces. Also, the relationship between this type of space and several other known types of spaces and functions has been dealt with.
Keywords: Swopen set; Seminormal space; Swregular space; Swnormal space; Somewhat open function; Swirresolute function